Investigating Concept Mastery of Physics Students During Online Lectures Through Rasch Models on Force and Motion Materials - Sulman, Fauzan; Yuliati, Lia; Kusairi, Sentot; Hidayat, Arif; Pentang, Jupeth Toriano; Mensah, Bismark (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2023)
Conceptual understanding and problem solving is the most crucial part of Physics Lectures. In lectures, mastery of the concept is the primary goal. This research aims to analyze students' mastery of physics concepts in the material of Force and Motion while lectures are conducted online. This study uses a mixed-method approach to explain students' answers that still need clarification. Data analysis was carried out using the Rasch model, and a questionnaire was developed based on the possibility of students' responses to the concepts of force and motion. The results of this study indicate that students' understanding of the concept of force and motion material still needs to improve, namely 64.062%, around 94% of glasses tadris students think that the force and motion material given by lecturers during exams is challenging. More than 60.94% of students believe this is because the ability of the force and motion material they have still needs to improve. These results are interpreted based on analysis through the winstep application Version 3.65.0. and for qualitative data obtained from interviews. It takes a learning model that is appropriate for use in online and offline learning.